Prediction of severe accident occurrence in radiation laboratory using fault tree method - Jasrin, Nurin Saqinah; Othman, Siti Amira; Nor Azman, Nor Farah Amirah; Abu Bakar, Nurul Fathihah
This paper reviews the prediction of severe accident occurrence in radiation laboratory using fault tree method. Accident can be happened everywhere either near-miss or not. Accident includes any unintended event including operating errors, equipment failures or other mishaps and the consequences or potential consequences of which are not negligible from the point of view of protection and safety. The primary benefit of fault tree (FT) method is it provides a unique insight into the operation and potential failure of a system. The FT process may lead to a single component or material that causes many paths to failure thus improving that one element may minimize the possibly of many failures. Besides that, by using the logic of a detailed failure analysis and suitable tools, FT helps the system focus on the causes of each event in a logical sequence that leads to the failure.